(untitled) (Dentika: Dental Journal, 2014)
Propolis is a resinous hive product, collected by bees from tree buds and mixed with secreted bee wax in order to avoid bacterial contamination in the hive, and also to seal it. It is acknowledged that propolis has antimicrobial activity as well as anti-inflammatory, antioxidant, antitumor, immuno-regulatory, and regenerative tissue properties. Chemically, propolis is exceedingly complex and contains a rich variety of potent terpene, benzoic, caffeic, cinnamic, aromatic aldehyde, phenolic acid, and also high in flavonoid. Recently, propolis has been the subject of several studies, both in vitro and in vivo or even at animal or human with the aim to elucidate its biological and pharmacological properties. The use of propolis in dentistry has been done in few years ago for various purposes such as in treatment of periodontitis and dental caries, to accelerate the healing of post-extraction wounds, to treat aphthous stomatitis, as a storage media following teeth avulsion. The result of basic research of propolis apparently was useful to support its clinical application in dentistry. However, standardization the composition of propolis due to its chemical diversity is still a problem. Therefore the purposes of this review article were (1) to explain the prospect of propolis in conservative dentistry and endodontic treatment, and (2) to stimulate the interest of clinicians to make further research about this natural compound in dentistry. In conclusion, propolis is a natural medication with a promising future but further studies should be conducted to investigate its merit and demerits in clinical dentistry